130 A pilot study of a timed short addition test as a tool for the longitudinal study of cognitive dysfunction in multiple sclerosis. Issue 3 (9th February 2012) - Cossburn, M; Moore, P; Baker, K E; Pickersgill, T P; Robertson, N P
Abstract : Cognition is a routinely measured in Multiple Sclerosis (MS) clinical trials using the Paced Auditory Serial Addition Task (PASAT) which tests arithmetic processing via a 60 element, time-paced list of single digits for addition. PASAT provides validated, longitudinal data but is rarely used outside trials as it is time consuming and requires audio equipment not routinely available in clinics. A quick, simple alternative would offer the opportunity to collect data currently missing from most clinical and epidemiological studies. We have piloted a timed short addition test (TSAT) comprising 10 serial digit-pair additions of the integers 1–10, in a predetermined order with the number of correct answers and time taken to perform the test recorded; correlating its performance with PASAT as a longitudinal measure of cognition. A total of 219 observations were made in 42 patients over 2 years, with a median of five tests per patient (range: 3–6). Mean baseline PASAT score was 44.9 (SD 10.1), baseline TSAT score 7.6(SD 2.1) and TSAT time 35.7 s (SD 11.4). There was close correlation between PASAT and TSAT (r 2 =0.74, p=0.001). TSAT was sensitive to change in PASAT (p<0.001), reliable (Cronbach's α 0.81) and reproducible. This pilot study suggests a simple TSAT provides information on longitudinal cognitive performance equivalent to PASAT. If reproduced in larger studies this suggests that it is possible to collect valid data on cognition in clinic settings.